Usability and acceptability assessment of an empathic virtual agent to prevent major depression. Issue 4 (25th May 2016) - Bresó, A.; Martínez‐Miranda, J.; Botella, C.; Baños, R. M.; García‐Gómez, J. M.
Abstract: In Human–Computer Interaction, the adaptation of the content and the way of how this content is communicated to the users in interactive sessions is a critical issue to promote the acceptability and usability of any computational system. We present a user‐adapted interactive platform to identify and provide an early intervention for symptoms of depression and suicide. In particular, we describe the work performed to assess users' system acceptability and usability. An empathic Virtual Agent is the main interface with the user, and it has been designed to generate the appropriate dialogues and emotions during the interactions according to the detected user's specific needs. This personalization is based on a dynamic user model nurtured with clinical, demographical and behavioural information. The evaluation was performed with 60 participants from the university community. The obtained results were promising, allowing the execution of a further clinical trial. The system's usability score was 75.7%, and the score of the user‐adapted content and the emotional responses of the Virtual Agent was 70.9%.